2016
DOI: 10.1007/s00213-016-4316-8
|View full text |Cite
|
Sign up to set email alerts
|

Delay and probability discounting by drug-dependent cocaine and marijuana users

Abstract: These results are inconsistent with the idea that steep discounting of both gains and losses and both delayed and probabilistic outcomes reflects a general impulsivity trait, as well as with the idea that all drug-dependent individuals are steep discounters. Rather, differences in discounting appear to be related to both the type of outcome and the specific drug on which individuals are dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
7
34
1
Order By: Relevance
“…It is interesting that analysis of the AuCs revealed that tasks that showed similar amount effects loaded on the same factors (i.e., delay and effort on Factor 1, and probability and social on Factor 2; see Table 4). The present finding of a correspondence between type of discounting and factor loading has not been reported previously, but it fits neatly with the previous finding that whereas delay and probability discounting load on separate factors, the discounting of losses, which does not show amount effects, loaded on yet a third factor (Mejía-Cruz, Green, Myerson, Morales-Chainé, & Nieto, 2016). Taken together, these results suggest that amount effects may reflect something more fundamental about the different types of discounting than just their susceptibility to the effect of amount.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is interesting that analysis of the AuCs revealed that tasks that showed similar amount effects loaded on the same factors (i.e., delay and effort on Factor 1, and probability and social on Factor 2; see Table 4). The present finding of a correspondence between type of discounting and factor loading has not been reported previously, but it fits neatly with the previous finding that whereas delay and probability discounting load on separate factors, the discounting of losses, which does not show amount effects, loaded on yet a third factor (Mejía-Cruz, Green, Myerson, Morales-Chainé, & Nieto, 2016). Taken together, these results suggest that amount effects may reflect something more fundamental about the different types of discounting than just their susceptibility to the effect of amount.…”
Section: Discussionsupporting
confidence: 93%
“…Jones and Rachlin (2009) found that delay, probability, and social discounting were positively correlated, and Mitchell (1999) reported weak but positive correlations between delay, probability, and effort discounting. However, using multiple measures of delay and probability discounting, others have found that they load on separate factors Mejía-Cruz et al, 2016), and they also loaded on separate factors in the present study, indicating that these two types of discounting involve separate traits. In any case, it should be noted that positive correlations between delay and probability discounting are the opposite of what would be expected if both reflected a single impulsivity trait, because whereas steep delay discounting could be construed as reflecting impulsivity, steep probability discounting corresponds to risk aversion rather than risk taking (Green & Myerson, 2010).…”
Section: Discussioncontrasting
confidence: 56%
“…Research of TD in relation to addictive behaviour has shown that increased rates of TD predict initiation and/or future use of cigarettes and cocaine in high-school students (Audrain-McGovern et al, 2009;Ayduk et al, 2000) . Moreover, individuals who smoke or are dependent on opioids, cocaine or methamphetamine (Hofmeyr et al, 2016;Mejia-Cruz et al, 2016;Robles et al, 2011) display increased rates of TD and higher rates of discounting is proposed to be an index of dependence severity (Amlung et al, 2016). Following a variety of treatments (e.g.…”
Section: Temporal Discountingmentioning
confidence: 99%
“…We hypothesized that AD is characterized by more impulsive decision-making within these facets compared with healthy controls, which would be indicated by lower probability discounting for gains, lower probability discounting for losses, and lower loss aversion. While some studies found the assumed group differences between samples with SUD (Bernhardt et al 2017 ; Brevers et al 2014 ) or ND and healthy controls (Brevers et al 2012 ; Holt et al 2003 ; Li et al 2016 ; Lorains et al 2014 ; Madden et al 2009 ), there were also studies that found no or opposite evidence in SUD (Mejía-Cruz et al 2016 ; Ohmura et al 2005 ; Reynolds et al 2004 ; Takahashi et al 2009 ) and ND (Gelskov et al 2016 ; Giorgetta et al 2014 ; Takeuchi et al 2015 ). Previous studies mostly used one decision-making task and found mixed evidence.…”
Section: Introductionmentioning
confidence: 99%